PERPUSTAKAAN DIGITAL DALAM KACAMATA HUKUM - Zulfikar Ghazali (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
The purpose of this research is to know and see how the position of digital libraries in a legal perspective. This type of research is qualitative with literature review data sources. Meanwhile, this literature review is carried out in four stages consisting of: (1) searching for literature that is in accordance with the problem to be studied or researched by scanning the literature efficiently, using both manual and online methods, (2) assessing literature through a number of criteria, including the source itself, the author and the subject, (3) systematically examining and analyzing literature content, and (4) critically and deeply synthesizing literature content from literature such as the book or papers reviewed. For the research results, it can be seen that digital libraries that serve and distribute collections in digital format have both positive and negative sides. On the one hand, it provides easy access that can reach users around the world. This is where the advantage of digital libraries is that they are called libraries without walls. However, on one hand, the existing content in the library can be adapted and changed very easily. Dissemination of information through digital libraries makes plagiarism possible and seems less legality. Digital collection storage is also vulnerable to damage caused by cybercrime. But fortunately, in every country there is already something that regulates damage and violations committed in the digital realm. So that users do not need to be afraid in expression and creativity using technology. As long as you know the legal rules related to digital objects. In Indonesia, electronic transactions and intellectual property rights are regulated by law. So there is no concern in disseminating information in the form of digital objects. Libraries as institutions that educate the nation's life are institutions that are authorized to disseminate legal information